Rethinking the eidos, genos, and diaphora of the health utility concept: a psychological perspective - Broekharst, Damien S. E.; Bloem, Sjaak; Groenland, Edward A. G.; van Raaij, W. Fred; Jeurissen, Patrick P. T.; van Agthoven, Michel (Frontiers in Psychology, 2023)
The notion of utility gained a strong foothold in health economics over the last decades. However, the concept of health utility has not yet been decisively or irrefutably defined and the definitions that exist often do not take into account the current state of psychological literature. This perspective paper shows that the current definition of health utility emphasizes decision-making processes, deploys personal preferences, assumes psychological egoism, and attempts to objectively and cardinally measure utility. However, these foundational axioms that underly the current definition of health utility are not necessarily in concurrence with the current state of psychological literature. Due to these perceived shortcomings of the current health utility definition, it may be beneficial to redefine the concept of health utility in accordance with the current state of psychological literature. In order to develop such a revised definition of health utility the commonly deployed formula (Eidos = Genos + Diaphora) originating from Aristotle’s metaphysics is applied. The revised definition of health utility proposed in this perspective paper alludes to health utility as ‘the subjective value, expressed in terms of perceived pain or pleasure, that is attributed to the cognitive, affective and conative experience of one’s own physical, mental and social health state, which is determined through self-reflection and interaction with significant others’. Although this revised definition does neither replace nor supersede other conceptualizations of health utility, it may serve as a refreshing avenue for further discussion and could, eventually, support policymakers and health economists in operationalizing and measuring health utility in an even more accurate and veracious manner.